Thermal Design Method for Optimization of Dry Heat Transfer through Hemp-Based Knitted Fabrics - Snežana B. Stanković; Sanja Pavlović; Matejka Bizjak; Dušan M. Popović; Goran B. Poparić (Journal of Natural Fibers, 2022)
In the present research, folding of yarns was applied as a method for designing thermal transport characteristics of hemp-based knits. The rib-knitted fabrics were made by combining one of two cotton two-folded yarns (differing in folding twist) with one of the two complex hemp yarns. The parameters describing the thermal properties in the steady-state and transient regimes of heat transfer were determined. The results indicated that the packing density of the fibers in the yarn plays a crucial role in the heat conduction through the fabric. The two-assembled hemp component appeared to be the main heat conductor in the knitted fabrics containing it. Between the knits composed of the two-folded hemp and two-folded cotton yarns, that having two-folded more twisted cotton yarn as a component was characterized by higher thermal conductivity. The higher thermal conductivity resulted in higher thermal absorptivity, but not necessarily in higher thermal diffusivity, as the increased volumetric heat capacity may limit the speed of heat spreading through the fabric. Therefore, the knits containing two-assembled hemp yarn differed in thermal diffusivity despite their similar thermal conductivity. Both knits with the two-folded more twisted cotton yarn as a component had similar thermal diffusivity despite their different thermal conductivity.